Модель оптимизации привлекательности банка в условиях ограниченных ресурсов - Годлевский, Михаил Дмитриевич; Дабагян, Давид Александрович (НТУ "ХПИ", 2017)
Предлагается модель оптимизации привлекательности банка на основе ряда критериев, заданных экспертами. Модель содержит иерархию критериев, построенную с помощью метода анализа иерархий. Важность критериев определялась с помощью метода парных сравнений Саати. Проводится параметрический анализ важности критериев для оценки степени влияния критерия на оценку банка. На основе этого анализа, формируется математическая модель решения задачи распределения инвестиций по данным критериям оптимальным образом.

A model is proposed for optimizing the attractiveness of the bank on the basis of a number of criteria set by experts. The model contains a hierarchy of criteria built using the hierarchy analysis method. The importance of the criteria was determined using the Saati pair comparison method. A parametric analysis of the importance of the criteria for assessing the degree of influence of the criterion on the assessment of the bank is carried out. Based on this analysis, a mathematical model of solving the problem of investment distribution according to these criteria is formed in the optimal way. The resource allocation problem is solved using the simplex method.
Model for optimizing the attractiveness of a bank in conditions of limited resources
Keywords: экономика; метод парных сравнений; оценка привлекательности банка; задача распределения ресурсов; оптимизация функционирования банка; метод анализа иерархий; paired comparison method; bank attractiveness evaluation; resource allocation problem; optimization of banking process; hierarchy analysis method